False data detection and dynamic selection of aggregator nodes with pair-wise key establishment in homogeneous wireless sensor networks. (2018) - Sandhya, M.K.; Murugan, K.; Devaraj, P.
Compromised sensor nodes inject false data in wireless sensor networks which distorts data integrity and consumes battery power unnecessarily. In the existing false data detection schemes, the aggregator nodes suffer from rapid battery drain due to the computational overhead, leading to reduced network lifetime. To avoid this, the aggregator nodes must be dynamically selected from the sensor nodes in the network. This dynamic selection of aggregator nodes introduces security challenges in symmetric key exchange among the sensor nodes. In this paper, a scheme called, false data detection-dynamic selection of aggregator nodes is proposed to address these issues. This scheme discards the false data injected into the network and also prolongs the network lifetime by the dynamic selection of aggregator nodes. The problem of symmetric key exchange arising due to the dynamic selection of aggregator nodes is resolved by the proposed Chebyshev polynomial-based pair-wise key establishment which has lesser computational overhead and offers better security strength. Simulation results indicate that the scheme eliminates false data injected by multiple compromised nodes and also offers higher network lifetime in homogeneous wireless sensor networks.